When I Hear the Word Migrant... Research on Images and Stereotypes with Sentence Completion Technique - Veutro, Maria Fobert (Italian Sociological Review, 2020)
In 2016 I conducted a study on the images of migrants, interviewing 100 people living in a small Sicilian town. We used a tool that I created ad hoc, inspired by the Sentence Completion Test. Subjects were asked to complete 44 incomplete sentences. Here are some examples: About immigrants I like..., The ethnic groups I know are..., Immigrants think that we Italians are, Romanian women..., etc. The analysis can be carried out with both quantitative procedures– classifying the completions of each sentence – both qualitative, like in this investigation, interpreting protocol by protocol the completions of each subject also in the light of the same subject’s completions of the other sentences. The results obtained encourage us to consider the instrument used as valid: for the most part it does not offer pre-established meanings and it seems effective in detecting deeply internalized values. Two of the problems that have emerged regard the alarm about the danger of dissolving our culture and traditions, and the unpleasant impression of stubborn attitudes of isolation and the reluctance of foreigners to integrate in the context of acceptance. Regarding attitudes towards foreign women, it has emerged that Romanian women appear enterprising, strong, free, and ‘breadwinners’ – they deviate from the classic female model and therefore cause concern; unlike Muslim women, who are considered to be weak and submissive. As for the words to be used, what emerged suggests the term ‘migrant’ rather than ‘immigrant’ should be used because the former promotes empathy and identification. Moreover, the term ‘foreigner’ should be preferred to ‘non-EU national’ because the latter probably arouses a greater sense of foreignness and distance and therefore is a little more threatening.